1945
DOI: 10.1104/pp.20.3.412
|View full text |Cite
|
Sign up to set email alerts
|

STARCH AND SUGARS OF VITIS VINIFERA

Abstract: were cut between 7 and 8 A.A. and taken directlv to the laboratory. The leaves w-ere promptly stripped off, and comparatively large samples of young anid of mature leaves were taken. Then 4-to 6-incll sections were removed from the base, middle, and tip of each shoot. The base and middle sections were divided into wood and bark. All samples were quickly cut into small pieces, weighed, and rapidlv dried in a small fruit dlehvdrater with a verv strong air blast at 600 to 630 C. The vines were cane pruned so that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
31
2
3

Year Published

1960
1960
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 13 publications
8
31
2
3
Order By: Relevance
“…The initial starch content of 12% is, on the one hand, similar to the late autumn maximum contents of canes reported for example by Winkler and Williams (1945) and Eifert, Panczel, and Eifert (1961). These authors and others have found a marked fall in starch and a corresponding rise in sugars during winter under natural conditions, followed by a partial reversal to give a second starch peak in early spring.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The initial starch content of 12% is, on the one hand, similar to the late autumn maximum contents of canes reported for example by Winkler and Williams (1945) and Eifert, Panczel, and Eifert (1961). These authors and others have found a marked fall in starch and a corresponding rise in sugars during winter under natural conditions, followed by a partial reversal to give a second starch peak in early spring.…”
Section: Discussionsupporting
confidence: 62%
“…A value of roughly 0·09 mg CO 2 /g fresh weight/hr was obtained, corresponding to some 0·37 g CO 2 for two-node cuttings for the period between the two harvests. This value is considered very high for woody tissue, and Winkler and Williams (1945) have pointed out that misleading results may be obtained in measuring cane respiration by means of CO 2 evolution, but it appears that respiratory needs of the cane may be of the same order as reserves utilized between harvests 2 and 3. However, the mention of two other possible reasons for the greater (absolute) reserve loss by two-node canes at this time is considered warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The storage of non-structural CHO is generally greatest in the root tissue of grapevines (Bates et al 2002, Uys andOrffer 1983), and root-derived CHO was found to be the principal reserve source for the annual resumption of growth in grapevines (Bates et al 2002, Loescher et al 1990, Zapata et al 2004. Reserve CHOs accumulate to their greatest concentrations in all plant organs by leaf fall in autumn (Bennett et al 2005, Williams 1996, Winkler and Williams 1945 and are mostly retained during ectodormancy (abbreviated to 'dormancy' throughout this work), apart from small respiratory losses. During leaf senescence in autumn, hydrolytic enzymes break down leaf proteins, CHO, and nucleic acids that are transported in the phloem back into the permanent plant structure, where they are stored during dormancy and remobilized in spring for early growth.…”
mentioning
confidence: 99%
“…Although the roots are considered the most important sites of accumulation of carbohydrates as regards vine reserves (Winkler & Williams, 1945;Scholefield, Neales & May, 1978), the primary goal of the viticulturist is to divert carbohydrates to the grapes in order to obtain high quality. Sugar accumulation in the fruit can either be directed from photosynthesis or mobilized from stored carbohydrate reserves in the roots, canes and trunk (Mansfield & Howell, 1981).…”
mentioning
confidence: 99%